A formação de educadores sexuais: possibilidades e limites - Figueiró, Mary Neide Damico [UNESP] (2001)
The aim of this research was to think about the continuity of formation of teachers turned to a positive and humanizing performance in Sexual Education, trying to understand the process of constructing the teaching knowledge and know how in Sexual Education, in the school daily life. The consideration was taken based on the study of the case of the experience in formation of educators carried out in Universidade Estadual de Londrina / PR (UEL). Such experience was composed of two moments. In the first one, Study groups were developed, in 1997, in which teachers of several public schools took part. There were three groups having approximately twenty people each, that got together once a week to discuss about Sexual Education. In the second moment, in1998, ten female teachers and one male teacher, who took part of the previous moment, began taking part of the Guiding group, a fortnight meeting which happened at the University, where they received supervision to the practical work and kept on the studies, debates and group reflection. The criteria to join it was to develop a Sexual Education program for children or teenagers. As a general result, eight teachers were successful, they got to develop a program and three of them partially attended to the demands, showing some difficulties. The reflection about the process of the continuity of formation of the ones who were successful, as well as of the ones who didn’t, brought about contributions to the comprehension of the aim of the study of this Thesis. A year after the end of the Guiding Group, the participants were individually interviewed, in order to check how much they could achieve and move forward in their pedagogical practice. It was checked that, among nine teachers (because two of them retired at the end of 1998), only two teachers got to develop a systematic program of teaching sexuality, in their schools. However, it was found out, with everybody, several possibilities of the teaching knowledge and know how in Sexual Education, in the everyday life of the school practice, that contributed to the personal and professional development of each teacher, as well as to the process of constructing the professional identity of the whole teaching group. Restricting factors to the process were also checked, which were connected to personal matters, or to peculiarities of the teaching profession and/or to the job context. A second study of the case was also insert: the continuity of formation process lived by a teacher in a State School, during the elaboration of her thesis about the teaching of sexuality in Portuguese classes. If was proved that, to the continuity of the formation of Sexual Education teachers efficiency, it is necessary to follow the reflexive model of formation, in which the experience, the history of life, the pedagogical practice, the knowledge built by the teacher and the group reflection exercise are valued. It is important that formation work be long and systematic and that the practice be accompanied by assessors. It was concluded that the situations of apprenticeship generated were not equally formative for all the teachers, as well as they were not equally formative for the same teacher, in his varied moments of life and of work. The three kinds of knowledge that each teacher brings along (the experience, the knowledge of the subject he teaches and the pedagogical knowledge) were influenced in their development and they were responsible for different development among the various participants. I propose that there be investments (connected to the sexuality field) in the professional development of the teacher and, above all, in their personal improvement. That he be treated as an individual to whom the sexual reeducation is important and necessary and not only a way of achieving the Sexual Education of the students.